Olympic Ceremonialism and The Performance of National Character - Tzanelli, R. author. aut Link
XII, 165 p.
Keywords: This book examines the London 2012 opening and closing ceremonies and the handover to Rio 2016 as articulations of national and cosmopolitan belonging. The ceremonial performances supported imaginative travel and created a tornadóros: an ideal form of 'human' that manipulates audiovisual narratives of culture and identity for global audiences.